Metabolomic and transcriptomic analyses revealed potential mechanisms of Anchusa italica Retz. in alleviating cerebral ischemia–reperfusion injury via Wnt/β-catenin pathway modulation - Wenta Tan; Shuo Fu; Yufei Wang; Bojun Hu; Guiquan Ding; Li Zhang; Wen Zhang; Guanhua Du; Junke Song (Natural Products and Bioprospecting)
Abstract Anchusa italica Retz. (AIR), a traditional herbal remedy, is commonly applied in managing heart and brain disorders. However, its specific function and mechanism in acute cerebral ischemia–reperfusion injury (CIRI) are not fully understood. This research focused on the interventional effects and potential mechanisms of AIR extract (AIRE) in a rat model of CIRI. The model was established using the filament occlusion method, which involved blocking the middle cerebral artery for 1.5 h and then removing the filament to restore blood flow. Transcriptomic and metabolomic analyses were conducted to explore the molecular pathways and metabolites affected by AIRE. ATP level was measured using an ATP assay kit. Additionally, RT-qPCR and western blot tests were conducted to evaluate the influence of AIRE on the Wnt signaling pathway and mitochondrial function. Transcriptomic and metabolomic analyses indicated that AIRE regulated the Wnt signaling pathway in CIRI and modulated metabolites associated with mitochondrial energy metabolism, such as citrate and succinate. ATP assay result demonstrated that AIRE enhanced ATP production in CIRI. Further, RT-qPCR and western blot analyses revealed that AIRE activated the Wnt/β-catenin signaling pathway and corrected mitochondrial dysfunction. These results proposed that AIRE mitigated mitochondrial energy metabolism deficits in CIRI via the Wnt/β-catenin pathway. By restoring the balance of mitochondrial function and energy metabolism, AIRE might offer a potentially therapeutic strategy for addressing CIRI. Graphical Abstract